2008
DOI: 10.1262/jrd.20054
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Hedgehog Family Genes in the Rat Uterus During Early Pregnancy

Abstract: Abstract. Hedgehog (Hh) plays a pivotal role in various tissues during embryonic development, tissue homeostasis and tumorigenesis. In mammals, Hh exists in three homologs: Desert hedgehog (Dhh), Indian hedgehog (Ihh) and Sonic hedgehog (Shh). In this study, we cloned full-length cDNAs encoding Dhh and Ihh from the rat uterus. Their amino acid sequences have a high homology with those of the mouse and human. In addition, the changes of Hh gene expression in the rat uterus during early pregnancy were analyzed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…On day 4, Ihh expression decreases in the luminal epithelium but remains high in the glandular epithelium . Patterns of Ihh expression in pregnant rats and hamsters are similar to that in the mouse (Khatua et al 2006, Kubota et al 2008. Treatment of ovariectomized mice with progesterone increased expression of Ihh in luminal and glandular epithelium , Takamoto et al 2002; the effect of progesterone was reduced in progesterone receptor (PGR) null mice (Takamoto et al 2002), providing evidence that Ihh is a target of signaling through PGR.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…On day 4, Ihh expression decreases in the luminal epithelium but remains high in the glandular epithelium . Patterns of Ihh expression in pregnant rats and hamsters are similar to that in the mouse (Khatua et al 2006, Kubota et al 2008. Treatment of ovariectomized mice with progesterone increased expression of Ihh in luminal and glandular epithelium , Takamoto et al 2002; the effect of progesterone was reduced in progesterone receptor (PGR) null mice (Takamoto et al 2002), providing evidence that Ihh is a target of signaling through PGR.…”
Section: Introductionmentioning
confidence: 78%
“…In addition, mRNA levels of Hhip and CouptfII, genes for which transcription is increased by HH signaling, were also elevated in the epithelium and periepithelial stroma (Takamoto et al 2002). In rats, the downstream target gene of HH signaling, Gli1, was expressed in the luminal epithelium as well as in the stroma on day 3.5 of pregnancy (Kubota et al 2008). In the current study, quantitative RT-PCR showed expression of components of the HH signaling pathway typical of target cells in luminal epithelium of uteri on day 4 of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, similar to the mouse, expression of components of the HH signaling pathway increases around the time of implantation in rats (Kubota et al, 2008;Kubota et al, 2010) and hamsters (Khatua et al, 2006). In another experiment, pieces of uterus in which the luminal epithelium was enzymatically removed were cultured in vitro.…”
Section: Hedgehog Signaling Pathway and The Frtmentioning
confidence: 99%
“…and Gli transcription factors -in mice (Lee et al, 2006a;Matsumoto et al, 2002;Takamoto et al, 2002), hamsters (Khatua et al, 2006), rats (Katayama et al, 2006;Kubota et al, 2008;Kubota et al, 2010), and humans (Wei et al, 2010). Cre sequence was inserted into the Pgr locus (Franco et al, 2010b).…”
Section: Ptch1mentioning
confidence: 99%
See 1 more Smart Citation